FACTIBILIDAD ECONÓMICA Y AMBIENTAL DEL HORMIGÓN PREFABRICADO EN ESTRUCTURAS DE TECHOS DE VIVIENDAS EN CONJUNTOS HABITACIONALES (Journal on studies and research of academic knowledge, 2008)
The objective of studying the economical and environmental feasibility of precast reinforced concrete usage for structural roof systems in housing areas as a first goal, carries out the research proposing the use of precast reinforced concrete substituting traditional technology using endemic timber, as an economic and environmental alternative for housing building, carried out by the EBY for people affected by the YACYRETA Hydroelectric dam impounfing and for other living areas forseeing the deficit of housing in Paraguay.The research applies the qualitative method, in a descriptive form and focus in technological alternatives. There was an experts conference as an application of Delphi method, with building construction enterprises, institutions, manufacturers and building materials deslers and suplyiers representatives and with specialists in environmental issues. Result show that: a) The precast reinforced concrete fulfils with the requirements of resistance and structural stability demanded b) it is economically feasible c) Using the precast reinforced concrete, solves the problem of manufacturers in the construction area in Itapúa. d) The proposed technology will soften this impact. e) The innate Paraguayan adaptability to changes makes easier the proper application of this technology.
Keywords: Technological alternative; Roof structure; Precast reinforced concrete; Environmental impact